Legal Standing of Courier Expedition That Sends Narcotics Without Knowledge - Yeffris Arya Dirgantara; Sri Anggraini Kusuma Dewi; Priambodo Adi Wibowo (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
This research aims to determine the legal position regarding expedition couriers who send narcotics without any element of knowledge. This research method uses normative research, with a conceptual approach, namely legal research that looks for principles, doctrines and sources of law in a philosophical sense. juridical. The result of an expedition courier accidentally sending narcotics, without knowing the contents of the package he sent, has the potential to obtain legal protection in certain situations. The relevant principle of criminal law is that a person cannot be convicted without an element of guilt (mens rea) or malicious intent.